2017
DOI: 10.1371/journal.pone.0187223
|View full text |Cite
|
Sign up to set email alerts
|

Patients with MDR-TB on domiciliary care in programmatic settings in Myanmar: Effect of a support package on preventing early deaths

Abstract: BackgroundThe community-based MDR-TB care (CBMDR-TBC) project was implemented in 2015 by The Union in collaboration with national TB programme (NTP) in 33 townships of upper Myanmar to improve treatment outcomes among patients with MDR-TB registered under NTP. They received community-based support through the project staff, in addition to the routine domiciliary care provided by NTP staff. Each project township had a project nurse exclusively for MDR-TB and a community volunteer who provided evening directly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…To address this issue all patients in Amhara region received food packages obtained from the global fund but they are not very adequate. Economical support and early nutritional intervention has been shown to reduce the mortality of MDR-TB patients [28, 39], and in resource-limited settings, profound undernutrition and gastrointestinal toxicities have been noted during MDR-TB treatment [37]. Malnutrition is also a predisposing factor for impaired host immunity to TB.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue all patients in Amhara region received food packages obtained from the global fund but they are not very adequate. Economical support and early nutritional intervention has been shown to reduce the mortality of MDR-TB patients [28, 39], and in resource-limited settings, profound undernutrition and gastrointestinal toxicities have been noted during MDR-TB treatment [37]. Malnutrition is also a predisposing factor for impaired host immunity to TB.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies that provided socioeconomic or psychosocial support during treatment reported treatment success among at least 71% of children and adolescents with tuberculosis. 55 58 , 62 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, as a first ever study, we aimed to assess whether the Union’s CBMDR-TBC project improved treatment initiation in patients diagnosed with MDR-TB. The effect of CBMDR-TBC project on unfavourable outcomes and death among registered patients during initial 8 months of treatment is published elsewhere [ 10 ].…”
Section: Introductionmentioning
confidence: 99%